2017
DOI: 10.1016/j.biopsych.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Avoidance in Mood and Anxiety Disorders Using Reinforcement Learning

Abstract: BackgroundSerious and debilitating symptoms of anxiety are the most common mental health problem worldwide, accounting for around 5% of all adult years lived with disability in the developed world. Avoidance behavior—avoiding social situations for fear of embarrassment, for instance—is a core feature of such anxiety. However, as for many other psychiatric symptoms the biological mechanisms underlying avoidance remain unclear.MethodsReinforcement learning models provide formal and testable characterizations of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
131
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(161 citation statements)
references
References 30 publications
(54 reference statements)
15
131
0
Order By: Relevance
“…Furthermore, reported anti-depressant effects of tVNS may partly rely on reduced learning, especially from punishments, as this may compensate for the reported increased punishment sensitivity in depressed patients [46,69]. More broadly, reduced dependence on learned contingencies may also offer the possibility to prevent overreliance on learned action-outcome combinations and encourage exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reported anti-depressant effects of tVNS may partly rely on reduced learning, especially from punishments, as this may compensate for the reported increased punishment sensitivity in depressed patients [46,69]. More broadly, reduced dependence on learned contingencies may also offer the possibility to prevent overreliance on learned action-outcome combinations and encourage exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, participant's choices in the tVNS condition were 'noisier' and less dependent on learned action values (Δξ = 0.035, p = .086, pboot = .050), although only nominally significant before correction for multiple testing. We also explored more complex models by additionally separating reward sensitivity and/or Pavlovian bias for reward and punishment as previously described [46]. However, these models did not provide a more parsimonious account at the individual level compared to the simpler models and individual estimates became increasingly unstable across iterations precluding their use to reliably estimate withinsubject stimulation effects (see SI).…”
Section: Tvns Reduces the Learning Rate In A Computational Model Of Bmentioning
confidence: 99%
“…With regard to social anxiety only the pathway between the putamen and middle cingulate cortex demonstrated increased connectivity. Both regions share functional connections (Hoffstaedter et al, 2012), thought to underlie the integration of emotion and motor-responses (Shackman et al, 2011), with stronger connectivity in this pathway during negative face possibly reflecting increased tendency to avoid or withdrawal negative social signals which constitutes a core feature of social anxiety disorders (Mkrtchian, Aylward, Dayan, Roiser, & Robinson, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Fitting these models to participants' choice behavior by adjusting model parameters allows for the assessment of group differences in various aspects of the learning process. Using this approach, it has been found that depressed participants are less sensitive to rewarding outcomes (Huys et al, 2013) but more responsive to punishments (Byrne et al, 2016;Mkrtchian et al, 2017) than controls. Additionally, depression has been associated with abnormalities in learning rate (Chase et al, 2010;Dombrovski et al, 2010;Beevers et al, 2013;Cooper et al, 2014) and exploration (Kunisato et al, 2012;Beevers et al, 2013;Rupprechter et al, 2018) parameters, with results suggesting that depressed individuals show suboptimal reward learning parameters.…”
Section: Introductionmentioning
confidence: 99%